2021
DOI: 10.1371/journal.pone.0251785
|View full text |Cite
|
Sign up to set email alerts
|

Physician skin cancer screening among U.S. military veterans: Results from the National Health Interview Survey

Abstract: Introduction Although military veterans are at increased risk for skin cancer, little is known about the extent to which they have been screened for skin cancer. The study objective was to examine the prevalence and correlates of physician skin cancer screening among U.S. military veterans. Methods Data were drawn from the National Health Interview Survey. The study sample consisted of 2,826 individuals who reported being military veterans. Receipt of a physician skin examination was measured using a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The CAPS participants also had a lower estimated prevalence of skin cancer screening compared to US military veterans. A cross‐sectional study using the 2015 National Health Interview Survey data for skin cancer screening by physicians among US military veterans reported that 30.8% of veterans had received screening 14 . Similar to the CAPS participants, these veterans were predominantly non‐Hispanic white (79.6%), male (91.3%), over two‐thirds (69.6%) had some college or higher education, and just over half (52.5%) perceived themselves to get sunburnt with prolonged sun exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The CAPS participants also had a lower estimated prevalence of skin cancer screening compared to US military veterans. A cross‐sectional study using the 2015 National Health Interview Survey data for skin cancer screening by physicians among US military veterans reported that 30.8% of veterans had received screening 14 . Similar to the CAPS participants, these veterans were predominantly non‐Hispanic white (79.6%), male (91.3%), over two‐thirds (69.6%) had some college or higher education, and just over half (52.5%) perceived themselves to get sunburnt with prolonged sun exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of American military veterans, a group at increased risk of melanoma due to exposure to UV radiation and barriers to sun protection during military actions, where high rates of sunburns and overrepresentation of older white men were present, less than one-third (30.88%) reported ever having a skin examination by a doctor. Among respondents reporting skin examination by a doctor, 35% had a family history of skin cancer, 39% had moderate to severe sunburns, and 30% used tanning beds [30]. In comparison to the mentioned analyses, individuals with risk factors for melanoma in the surveyed group of Silesian residents were provided insu cient healthcare and received rare preventive actions.…”
Section: Discussionmentioning
confidence: 99%